2009
DOI: 10.1016/j.ibmb.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The Anopheles gambiae salivary protein gSG6: An anopheline-specific protein with a blood-feeding role

Abstract: The Anopheles gambiae salivary gland protein 6 (gSG6) is a small protein specifically found in the salivary glands of adult female mosquitoes. We report here the expression of a recombinant form of the protein and we show that in vivo gSG6 is expressed in distal-lateral lobes and is secreted with the saliva while the female mosquito probes for feeding. Injection of gSG6 dsRNA into adult An. gambiae females results in decreased gSG6 protein levels, increased probing time and reduced blood feeding ability. gSG6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
70
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 49 publications
2
70
1
Order By: Relevance
“…Instead they perform complementary functions to optimize successful feeding. Our data and conclusions are supported further by data on the partial silencing of salivary apyrase and gSG6 genes in A. gambiae, which resulted in reduced mosquito feeding efficiency (33,34). Finally, our results support transgenic approaches for studies of gain and loss of salivary functions.…”
Section: Discussionsupporting
confidence: 85%
“…Instead they perform complementary functions to optimize successful feeding. Our data and conclusions are supported further by data on the partial silencing of salivary apyrase and gSG6 genes in A. gambiae, which resulted in reduced mosquito feeding efficiency (33,34). Finally, our results support transgenic approaches for studies of gain and loss of salivary functions.…”
Section: Discussionsupporting
confidence: 85%
“…This result does not correlate with an observation that gSG6 is conserved in five species members of the A. gambiae complex, i.e., A. gambiae, Anopheles melas, Anopheles bwambae, Anopheles quadriannulatus A, and Anopheles arabiensis (Lombardo et al 2009). The gSG6 protein was originally identified in A. gambiae in the form of a transcript specifically expressed in adult female salivary glands and predicted to encode a small secretory protein (Lanfrancotti et al 2002).…”
Section: Discussioncontrasting
confidence: 85%
“…The corresponding 10 kDa protein was highly expressed in the salivary glands of adult females (Francischetti et al 2002). Lombardo et al (2009) demonstrated that gSG6 was expressed in distallateral lobes and secreted with the saliva while the female mosquito probes for feeding. Injection of gSG6 dsRNA into adult A. gambiae females resulted in decreased gSG6 protein levels, increased probing time and reduced bloodfeeding ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations